Sentiment analysis and actor mapping in media coverage of the forced hijab case at SMAN 1 Banguntapan - Ine Yudhawati; Ana Nadhya Abrar; Novi Kurnia (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2025)
This study examines online media coverage of the alleged forced hijab case at SMAN 1 Banguntapan using actor mapping and sentiment analysis. Based on a quantitative content analysis of 72 news articles published during the peak period of the case (July 31–August 7, 2022), the findings show a strong dominance of negative sentiment and a concentration on institutional actors, while victims and civil society voices were marginalized. Media narratives largely emphasized conflict and polarization rather than reconciliation. Such framing may normalize exclusionary discourses, reinforce perceptions of intolerance, and constrain more inclusive understandings of religious diversity.